Are implicit motives revealed in mere words? Testing the marker-word hypothesis with computer-based text analysis - Schultheiss, Oliver C. (Frontiers in Psychology, 2013)
Traditionally, implicit motives (i.e., nonconscious preferences for specific classes of incentives) are assessed through semantic coding of imaginative stories. The present research tested the marker-word hypothesis, which states that implicit motives are reflected in word frequencies. Using Linguistic Inquiry and Word Count (LIWC; Pennebaker, Francis, & Booth, 2001), Study 1 identified word categories that converged with a content-coding measure of the implicit motives for power, achievement, and affiliation in picture stories collected in German and US student samples, showed discriminant validity with self-reported motives, and predicted well-validated criteria of implicit motives (gender difference for the affiliation motive; in interaction with personal-goal progress: emotional well-being). Study 2 demonstrated LIWC-based motive scores’ causal validity by documenting their sensitivity to motive arousal.